دراسة سريرية مقارنة بين الجسور الخزفية- المعدنية والجسور الخزفية الخالية من المعدن - عيسى, نزيه (Latakia University Journal -Medical Sciences Series, 2019)
الهدف من هذه الدراسة هو الحصول على معلومات سريريه مقارنه عن مزايا ومساوئ كل من التعويضات السيراميكية- المعدنية والتعويضات السيراميكية- الخالية من المعدن . تم إجراء التعويضات السيراميكية الخالية من المعدن من نظام IN-CERAM والتعويضات السيراميكية المعدنية من نظام OMEGA 900 من شركة VITA الألمانية لكل من المرضى الذين اختيروا لهذا البحث وعددهم /50/ مريضا وبعد مراقبة حالاتهم الفموية والسنية لمدة/ 3/ سنوات وتقييم هذه التعويضات من حيث : 1- ردود الفعل اللثوية . 2- الخصائص التجميلية تحت ظروف الإضاءة المختلفة . 3 -المتطلبات التقنية لهذه التعويضات عند التحضير 4- فشل هذه التعويضات جزئيا أو كليا. تم جمع المعلومات الخاصة بكل مريض على استمارة مصممة بشكل خاص يمكن إدخال مضمونها إلى البرنامج الإحصائي SPSS الذي استخدمت منه النسخة/ 11/ VERSION وبإجراء التحليل NON PARAMATRIC TEST تم الحصول على المعلومات الإحصائية التي تفيد بأفضلية التعويضات السيراميكية الخالية من المعدن من النواحي التالية : 1-العلاقة مع النسج ما حول السنية .الصحية والتجميلية . 2-المظهر التجميلي للتعويض ذاته تحت الأنواع المختلفة من الأضواء . أما من حيث الخصائص الأخرى فلم نجد بالدراسة الإحصائية اختلافات ذات دلاله وهذه الخصائص هي : 1-الحاجة لاستئصال الباب الأسنان بسبب التحضير . 2-الحاجة لتقوية الأسنان الداعمة بالاوتاد والقلوب بسبب التحضير : 3-فشل التعويض الجزئي أو الكامل ضمن فترة الدراسة . من هذه النتائج ننصح باستخدام الجسور السيراميكية الخالية من المعدن في حالات التتويج الإفرادي وحالات الجسور الثابتة –الثابتة لما لها من مزايا إضافية على الجسور السيراميكية المعدنية. The aim of this research is getting clinical information comparing between advantages of Metal- Ceramic bridges & Metal –free ceramic bridges and their disadvantages . The partially missing teeth of /50/ patients were replaced by these two systems of ceramic prostheses ; Omega/900/ & In-ceram , from VITA co. for every patient. Their mouths cases were watched for three years from points: 1- Periodontal tissues responses. 2-Esthitc properties under different kinds of light. 3- Clinical requirements of installing each system. 4- Partial or complete failure of each system . The results of checking up of the mouths cases were collected by a special designed forms . then these results were analysisd by SPSS program version /11/ for evaluating the important of the statistical differences .The statistical tests - non parametric test- refereed to: 1-The differences between the two types of bridges were significant statistically from the points : A- There were positive responses of periodontal tissues toward In- ceram bridges. Whereas Metal –ceramic bridges had many negative reaction. B-Esthetic properties of In-ceram bridges under deferent types of light .whereas the appearance of metal-ceramic bridges defers according to surrounding light 2- There weren't significant differences between the two types of bridges from points: A-The need to indodontic treatments B-The need to strengthen the abutments by post and core. C-Rate of partial ore complete mechanical failures of the two types of bridges . So ,we can conclude : that dentists can avoid esthetic & gingival negative response by using the in-ceram bridges instead of metal-ceramic bridges .without any confusion about its others properties